2023
DOI: 10.31234/osf.io/n75vc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agreement attraction in grammatical sentences and the role of the task

Abstract: This study evaluates two broad classes of language processing accounts that make predictions for sentences like “The admirer of the singer(s) apparently thinks...”. Feature distortion accounts predict increased processing difficulty at the verb in sentences with a plural distractor noun (singers) while similarity-based interference accounts predict the opposite: increased difficulty in sentences with singular distractor noun (singer). Neither of these effects was reliably observed in earlier research, and the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Likewise, the metanalysis of Jäger et al ( 2017 ) found evidence in favor of inhibitory interference in neither subject-verb agreement nor antecendent-reflexive structures. This is also in line with a recent meta-analysis and results of Laurinavichyute and von der Malsburg ( 2023 ), who found no evidence for inhibitory interference in grammatical sentences either in the hither-to published literature or in their own experiments using subject-verb agreement in English. Our study, therefore, sheds further doubt on these effects.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, the metanalysis of Jäger et al ( 2017 ) found evidence in favor of inhibitory interference in neither subject-verb agreement nor antecendent-reflexive structures. This is also in line with a recent meta-analysis and results of Laurinavichyute and von der Malsburg ( 2023 ), who found no evidence for inhibitory interference in grammatical sentences either in the hither-to published literature or in their own experiments using subject-verb agreement in English. Our study, therefore, sheds further doubt on these effects.…”
Section: Discussionsupporting
confidence: 90%
“…Laurinavichyute & von der Malsburg, 2022), but also the number of fillers. Possibly, task adaptation effects (Fine et al, 2013;Arehalli & Wittenberg, 2021;Laurinavichyute & von der Malsburg, 2023) may have influenced results of different studies to a different extent. Moreover, it is unlikely that more subtle differences in the methodologies of different experiments would have been replicated directly, for example, the wording of instructions, font sizes or the experimental software/platform.…”
Section: Agreement Attraction Effects In Comprehension Have Been Atte...mentioning
confidence: 99%
“…reflect differences in answering preferences occasioned by the different balance of nonsubject-like bare noun distractor/subject-like modified distractor conditions in Experiment 4. Hammerly et al (2019) and Türk (2022) show that response biases can change the qualitative pattern of agreement errors in acceptability judgment tasks (see also Laurinavichyute & von der Malsburg, 2023). Hammerly et al (2019) found that agreement attraction errors may vary with response bias, depending on whether participants expect the sentence they see to be ungrammatical to a lesser or greater extent.…”
Section: While the Qualitative Pattern Of Accuracy Findings Mirrors T...mentioning
confidence: 95%